PENGARUH PENCUCIAN DAN PENAMBAHAN CRYOPROTECTAN PADA KARAKTERISTIK SURIMI IKAN PATIN (Pangasius sp.) - H Hafiludin (Jurnal Kelautan, 2012)
Catﬁsh are traded in the form of whole ﬁsh and ﬁllet products. Catﬁsh are still notwidely used or processed into value added products. The purposeof this study was to determine the effect off requency of washing and frozen storage of catﬁsh surimi characteristics. The research was conducted with several stages, they were to determined the characteristics of raw materials and to made with indWerence of washing frequencies to determined the best surimi; second, this study also to determined the effect of storage duration on physical and chemical characteristics of catﬁsh surimi. The best of catﬁsh surimi production due with once washing. It was based on test of fold, teeth cutting and water content. Storage treatments and cryoprotectan additional give different results on the value of TVB, pH and water content catﬁsh surimi. The value of TV13, pH dan water content also increased. Hidoniktest (folding and teeth cutting test) also shows the different results between different treatment of both storage and cryoprotect an addition. During storage, the folding and teeth cutting test remains in good value which indicates deterioration in the quality of catﬁsh surimi occurred slowly.Keywords: catﬁsh, surimi, TVB, ﬁllet products